Odpowiedź :
Odpowiedź:
a) P = ( 1; -30)
x1 = - 2 x2 = 3
y = a*(x - x1)*(x -x2) = a*( x + 2)*( x - 3)
f(1) = - 30, więc
- 30 = a*( 1 + 2)*(1 - 3) = - 6 a / : (-6)
a = 5
y = 5*( x + 2)*( x - 3) = 5*(x² -3 x +2 x - 6) = 5*( x² - x - 6)
Odp. y = 5 x² -5 x - 30
========================
b) P = ( 1, -5) x1 = x2 = 4
f(x) = a*( x - 4)²
-5 = a*( 1 - 4)²
- 5 = 9 a / : 9
a = - [tex]\frac{5}{9}[/tex]
f(x) = - [tex]\frac{5}{9}[/tex] *( x - 4)² = - [tex]\frac{5}{9}[/tex] *( x² - 8 x + 16)
Odp. f(x) = - [tex]\frac{5}{9}[/tex] x² + [tex]\frac{40}{9}[/tex] x - [tex]\frac{80}{9}[/tex]
=========================
c) i d) analogicznie.
Szczegółowe wyjaśnienie: